PENYULUHAN PEMBERANTASAN SARANG NYAMUK KEPADA MASYARAKAT PASAR TIGA RINGROAD KECAMATAN MEDAN SUNGGAL - Tobing, Jerry Fitrio Julianto; Hutagalung, Sanggam B.; Butar-Butar, Harry; Hutahaean, Reinhard J. D.; Rimbun, Surjadi; Simanjuntak, Evirosa; Kautsar, Dinda; Sibarani, Chintya D. P.; Siahaan, Samuel D. J. (Universitas Methodist Indonesia, 2023)
The aim of community service activities is to implement community service in implementing the Tri Dharma of higher education as well as contributing ideas and transferring knowledge to mothers, fathers, children and youth. This service activity was carried out on March 17 2022, with the material Increasing Body Immunity. This topic is really needed in order to provide information and knowledge regarding the eradication of mosquito nests which prevents the transmission of disease from mosquitoes. This topic was deliberately chosen considering that Indonesia is a tropical country so the role of medical personnel is very important in providing education to the public to behave in a clean life at home and around the home environment, where this activity aims to reduce the risk of transmission and contracting diseases that cause mosquito bites which can cause death.